China and African Governance in the Extractive Industries - Neil Renwick; Jing Gu; Song Hong (Revue Internationale de Politique de Développement)
This paper examines China’s role in the extractive industry sectors of sub-Saharan Africa and issues surrounding governance—particularly the maximisation of host country economic gains. China’s involvement is controversial and the focus of international debate as to the extent to which Chinese–African relationships in this key sector are not ‘win–win’ but are damaging African partner economies and political cultures. The paper’s motivation is a desire to explain more closely the growing involvement of China in sub-Saharan Africa’s extractives sector in terms of how effectively African governance works to maximise the gains accruing to China’s African partners. A central question is how far there is Chinese synchronisation with the rules, principles, norms and behavioural expectations of African partners. The study assesses the experience of the Democratic Republic of Congo (DRC). Key findings are that China’s involvement takes many forms, but is heavily influenced by its own history as well as its emerging engagement with the international development assistance system. The DRC case demonstrates that the effectiveness of African regulatory regimes is highly variable and depends on the quality of governance. Africa has extensive regulatory and normative regimes that frame the Chinese relationship. However, to maximise gains to African partners, the Chinese state and Chinese firms must strengthen policy on corporate responsibilities and practice whilst African states must strengthen the quality of governance to turn political commitments into more robust practice.